Analysis and design of slitted waveguides with suppressed slot-mode using periodic FDTD. - Cameron, T.; Sutinjo, Adrian; Okoniewski, M. (IEEE, 2012)
The characteristics of the slot- and perturbed TE10 modes in a slitted waveguide are studied for the purpose of suppressing the undesired slot-mode. The use of the finite difference time domain (FDTD) with periodic boundary conditions allows the extraction of the individual complex waven umbers of the two modes, and thus the tracking of the modes as modifications are made to the structure. Two structures are presented, the first suppressing the propagation of the slot-mode, and the second suppressing the radiation of the slot-mode. Experimental validation is presented supporting the numerical results. It will be shown that a wide band suppression of the slot-mode propagation is achievable. However, there is a significant impact on the propagation characteristics of the desired perturbed TE10 modes. Conversely, the suppression of the slot-mode radiation is achievable with minimal impact on the perturbed TE10 mode.